An atypical case of sporadic fatal insomnia. Issue 8 (16th July 2009) - Priano, L; Giaccone, G; Mangieri, M; Albani, G; Limido, L; Brioschi, A; Pradotto, L; Orsi, L; Mortara, P; Fociani, P; Mauro, A; Tagliavini, F
Abstract : Fatal insomnia is a rare human prion disease characterised by sleep–wake disturbances, thalamic degeneration and deposition of type 2 disease-specific prion protein (PrP Sc ). This report details a patient with sporadic fatal insomnia who exhibited cerebral deposition of type 1 PrP Sc and neuropathological changes largely in the basal ganglia. Previous damage of this brain region by a surgically removed colloid cyst and the insertion of two intracerebral shunts may have influenced the distribution of PrP Sc through a chronic inflammatory process. These findings add to our knowledge of the phenotypic variability of human prion diseases with prominent sleep disturbances.